Republic of Mozambique : Staff Report for the 2002 Article IV Consultation, Fourth Review Under the Poverty Reduction and Growth Facility and Request for an Extension of the Poverty Reduction and Growth Facility Arrangement. (IMF Staff Country Reports; Country Report ;, 2002)
This paper examines the Republic of Mozambique's 2002 Article IV Consultation, Fourth Review Under the Poverty Reduction and Growth Facility (PRGF), and a Request for an Extension of the PRGF Arrangement. Economic activity in Mozambique has recovered strongly from the devastating floods that reduced growth in 2000 to less than 2 percent. The authorities are seeking a one-year extension of the current PRGF arrangement to allow full disbursement of the committed amount in support of the reform program. The IMF staff welcomes the priority given by the authorities to comprehensive public sector reform.